Bahan Ajar Multimedia Interaktif Kewirausahaan SMK Menggunakan model Pembelajaran Problem Based Learning - Yulian Findawati; Suprianto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
Currently there are no alternative materials other than text book teaching entrepreneurship. In this study the authors will mengembangankan interactive multimedia teaching materials entrepreneurship in vocational class X as an alternative teaching materials entrepreneurship. The Interactive Multimedia Instructional Materials using the Problem Based Learning approach in the form of learning method that uses problems as a first step in collecting and integrating new knowledge based on experience . Where the Problem Based Learning approach will be built in the form of interactive multimedia using Macromedia Flash MX . In accordance with the terminology used is problem based learning or problembased learning , the interactive multimedia teaching materials is an interactive multimedia teaching materials teaching materials the user to position for the character / characters prospective entrepreneurs who will know and solve the problem in which entrepreneurship tailored to the vocational curriculum class X. Interactive multimedia teaching materials testing will be conducted using a questionnaire by media expert and expert due diligence expected materi.upaya interactive multimedia instructional materials that are built to attract students to alternative learning entrepreneurship With the validation performed by media specialists and materials experts as efforts are expected to test the feasibility of an interactive multimedia instructional materials that are built to attract students to learn entrepreneurial